Clinical management and supervision of Influenza – systematic review - Michał Głodzik; Marek Miśkiewicz; Martyna Łęcka; Aleksandra Ogiegło-Kowalczyk; Julia Samborska; Karina Stelmaszak; Katarzyna Stencel; Paweł Więckowiak; Monika Wojtasik; Katarzyna Żak (Journal of Education, Health and Sport, 2024)
The main aim of the following study is to review current knowledge on Influenza.